Post-pandemic challenges: Person-organization fit, satisfaction and work adjustment for expatriate academics - Najihah Hanisah Binti Marmaya; Bamini KPD Balakrishnan (Human Resource Management Academic Research Society (HRMARS), 2025)
This study explores the work adjustment among expatriate academics in Malaysia during post covid 19. Specifically, this study examines the antecedents of expatriate academics’ job satisfaction and work adjustment in public universities in Malaysia. A quantitative method was adopted in this study and responses from 160 expatriate academics were analyzed using Structural Equation Modeling (SEM). The result showed that all of the hypotheses were supported. This result shows that expatriate academics were satisfied with their work environment when the needs that they possess related to work offered by their work environment. Job satisfaction was also found to link with work adjustment. This study adopts a cross-sectional research design and examined the opinions of expatriates at only one point in time. Longitudinal research design should be done for a better result. The result indicate that top management should focus on maintaining expatriates’ satisfaction to increase their level of work adjustment during post covid 19. This empirical study attempts to enrich the understanding of the work adjustment among expatriate academics in Malaysia.